Integration of Agricultural Education into the Merdeka Curriculum to Support the Projek Penguatan Profil Pelajar Pancasila (P5) at SMP PGRI 2 Somagede, Banyumas Regency - Syarifah, Risqa Naila Khusna; Suprayogi; Purwanto; Sofa, Eros Meilina; Bayyinah, Lafi Na'imatul; Novitasari, Dian; Pratama, Rama Adi; Hanifa, Hana; Ratnaningsih, Hanim Rahayuani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The community service program at SMP PGRI 2 Somagede, Banyumas Regency involves the integration of agricultural education into the Merdeka curriculum as part of the efforts to support the Projek Penguatan Profil Pelajar Pancasila (P5) and the development of school gardening potential. This activity takes a holistic approach by integrating practical agricultural education into the curriculum so that students are directly involved in soil preparation activities, preparation of planting materials, planting, harvesting and management of agricultural products. In addition, this project promotes the strengthening of Pancasila values such as mutual cooperation and social justice. In addition to being equipped with agricultural skills, students are encouraged to understand their role in building character in accordance with national values. This community service activity aims to enhance students’ practical skills in agriculture and enrich their understanding of moral and social values. The methods used in this activity include counseling, training and direct support to students and teachers of SMP PGRI 2 Somagede on cultivation techniques and the application of integrated farming. The results of this activity show that the application of drip irrigation technology and the processing of agricultural waste supports P5 and the development of the potential of school gardens. This activity not only improves the knowledge and skills of students, but also supports the optimization of school gardens in implementing integrated farming. It is expected that the success of this program will serve as a model for schools and villages in implementing the establishment of Agroeduwisata in Kemawi village, Somagede district, Banyumas local government area.